2004
DOI: 10.1038/sj.bjc.6601504
|View full text |Cite
|
Sign up to set email alerts
|

Additive antitumour effect of the epidermal growth factor receptor tyrosine kinase inhibitor gefitinib (Iressa, ZD1839) and the antioestrogen fulvestrant (Faslodex, ICI 182,780) in breast cancer cells

Abstract: A high expression level of epidermal growth factor receptor (EGFR)/HER1 has been suggested to lead to a shorter survival time and resistance to endocrine therapy in patients with breast cancer. To test the hypothesis that inhibition of the EGFR signalling pathway affects the antitumour effect of endocrine therapy, an EGFR tyrosine kinase inhibitor (EGFR-TKI), gefitinib, and an oestrogen receptor (ER) antagonist, fulvestrant, were administered to human breast cancer cells. A total of five human breast cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 34 publications
1
38
0
1
Order By: Relevance
“…Thus, the rescuing effect of Hrg was mediated through ErbB activation, likely through ErbB3 and/or ErbB4 dimerization with ErbB2. [14,37,38]. Our findings that Hrg is able to restore growth of fulvestrant-treated MCF-7 cells and that MCF-7 sublines with acquired fulvestrant resistance are more sensitive to pan-ErbB inhibition when maintained on fulvestrant suggest that combined treatment targeting ErbB and ERa signaling could be used to prevent or delay development of treatment resistance.…”
Section: Cetuximab But Not Trastuzumab or Pertuzumab Inhibits Growtmentioning
confidence: 83%
“…Thus, the rescuing effect of Hrg was mediated through ErbB activation, likely through ErbB3 and/or ErbB4 dimerization with ErbB2. [14,37,38]. Our findings that Hrg is able to restore growth of fulvestrant-treated MCF-7 cells and that MCF-7 sublines with acquired fulvestrant resistance are more sensitive to pan-ErbB inhibition when maintained on fulvestrant suggest that combined treatment targeting ErbB and ERa signaling could be used to prevent or delay development of treatment resistance.…”
Section: Cetuximab But Not Trastuzumab or Pertuzumab Inhibits Growtmentioning
confidence: 83%
“…A combination of an anti-estrogen with gefitinib, both of which could suppress the G 1 -S cell cycle transition by different mechanisms, could be beneficial. Recent results using breast cancer cells support the use of this combination (25).…”
Section: Introductionmentioning
confidence: 91%
“…It has been suggested that the cell-cycle retardation is mediated by the up-regulation of cyclin-dependent kinase inhibitors p21 and p27. 34,35 The induction of apoptosis is mediated by a decrease in the expression level of an anti-apoptotic protein Bcl-2 36 or by the activation of a proapoptotic protein BAD. 37 In this study, we confirmed that gefitinib induced apoptosis in cultured nontumorous BECs, which was associated with the inhibition of biliary cyst formation.…”
Section: Discussionmentioning
confidence: 99%